FAKTOR-FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN PLASENTA PREVIA PADA IBU BERSALIN DI RSUD DAYA KOTA MAKASSAR - yudiarsi eppang; Saharuddin (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2021)
The aim of the study: To determine the risk factors associated with the incidence of placenta previa in mothers who gave birth at RSUD Daya Makassar City. Method: Quantitative Research, with a cross sectional approach. The design of this study was used with the goal to knowing the risk factors associated with the incidence of placenta previa in mothers who gave birth at RSUD Daya Kota Makassar in 2020. The population in this study were all mothers who experienced placenta previa recorded as data in the INC room at RSUD. Daya City of Makassar in 2020. The sample in this study were women who experienced placenta previa recorded in the INC room data at RSUD Daya Kota Makassar in 2020. Results: This study shows that 15 respondents studied showed that there was a relationship between age, parity, history of curettage, and the distance between pregnancies to the incidence of placenta previa. Based on the results of the chi square test, the results obtained were age (p = 0.019), parity (p = 0.005), history of curettage (p = 0.020) and pregnancy distance (p = 0.020). Conclusion: in this study there is a significant relationship between age, parity, history of curettage, and the distance between pregnancies to the incidence of placenta previa at RSUD Daya Kota Makassar. Suggestion: Suggestions for health workers need to increase antenatal supervision of pregnant women who have a history of obstetrics, so that risky pregnant women can be managed properly